2022
DOI: 10.1002/evl3.299
|View full text |Cite
|
Sign up to set email alerts
|

Limited sex differences in plastic responses suggest evolutionary conservatism of thermal reaction norms: A meta-analysis in insects

Abstract: Temperature has a profound effect on the growth and development of ectothermic animals. However, the extent to which ecologically driven selection pressures can adjust thermal plastic responses in growth schedules is not well understood. Comparing temperature‐induced plastic responses between sexes provides a promising but underexploited approach to evaluating the evolvability of thermal reaction norms: males and females share largely the same genes and immature environments but typically experience different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 283 publications
1
5
0
Order By: Relevance
“…Females are often more sensitive to nutritional stress during the larval stage than males (Teder and Kaasik 2023). This is reflected in our study, where the allometric scaling of female reproductive organs showed more significant plasticity, suggesting that the female reproductive organ development is particularly sensitive to nutritional variations experienced during the larval stages.…”
Section: Plasticity In Allometric Growth Of Reproductive Organssupporting
confidence: 60%
“…Females are often more sensitive to nutritional stress during the larval stage than males (Teder and Kaasik 2023). This is reflected in our study, where the allometric scaling of female reproductive organs showed more significant plasticity, suggesting that the female reproductive organ development is particularly sensitive to nutritional variations experienced during the larval stages.…”
Section: Plasticity In Allometric Growth Of Reproductive Organssupporting
confidence: 60%
“…Theory provides multiple nonmutually exclusive explanations to account for Haldane's rule, including dominance theory (unmasked recessive DMIs linked to the hemizygous sex chromosome), faster male theory (production of DMIs from more rapid molecular evolution of genes with male‐biased expression, potentially due to sexual selection), fragile male theory (greater sensitivity of male developmental programs to generate DMIs), faster X theory (DMIs arising from potentially quicker molecular evolution of X‐linked genes), and genomic conflict theory (DMIs arising from cyto‐nuclear divergence or divergence in sex‐linked genetic drive elements) (Cowell, 2023; Hurst & Pomiankowski, 1991; Presgraves, 2010a; Turelli & Orr, 1995; Turelli & Orr, 2000; Wu & Davis, 1993; Wu & Davis, 1993). The fragile male hypothesis perhaps has the strongest implicit roots in development in that it supposes that there is something about the architecture of genetic networks that control development of male‐specific traits (such as gametogenesis) that are particularly sensitive to perturbation (Hunt & Hassold, 2002; Sage et al, 2015; Sharp & Agrawal, 2013; Yeh et al, 2018, but see Teder & Kaasik, 2023). However, the developmental causes for why, in general, the sexes differ in the sensitivity of traits to perturbation remain to be characterized.…”
Section: Rules Of Developmental Evolution In Speciationmentioning
confidence: 99%
“…Sex-specific susceptibility to early-life adversity has been demonstrated in some species, with negative associations between harsh developmental conditions and later-life phenotypes apparent in only one sex [2428]. When longevity differs between the sexes (e.g.…”
Section: Introductionmentioning
confidence: 99%